Preoblikovanje stanovanjskih objektov za potrebe družinskega podjetništva - Čok, Gregor (AR. Arhitektura, raziskave, 2005)
The sociological and economic rationale of working from home is causing certain spatial consequences that are reflected in the transformation of living environments. Thus residential buildings, as typologically complete units, are transforming their composition and layout and changing into multifunctional architectural hybrids. The article deals with classification of emergent physical solutions, which point out patterns of self-building practises, and shows possibilities for regulating the described processes.
Keywords: delo na domu; gospodarska poslopja; bivalno okolje; prostorske rešitve; arhitekturna ureditev